Remembering cold days : the 1942 massacre of Novi Sad, Hungarian politics, & society, 1942-1989 - Klimó, Árpád von, 1964- 1964- (Pitt series in Russian and East European studies, 2018)
"In Remembering Cold Days, von Klimó examines public contentions over the Novi Sad massacre from its inception in 1942 until the final trial in 2011, and reveals how attitudes changed over time toward this war crime and the Holocaust through different political regimes and in Hungarian society. The book also views how the larger European context influenced Hungarian debates, and how Yugoslavia dealt with memories of the massacre."